Understanding perceptions of stigma and accessibility for persons with disabilities in tourism infrastructure and public spaces the case of Quezon City - Nanca, Aileen E.; Morales, Mark Anthony M. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
This study investigated how perceptions of stigma and accessibility among Persons with Disabilities (PWD) are shaped by the Social, Biopsychosocial, and Geospatial Models of Disability within the context of tourism infrastructure and public spaces in Quezon City. It combines qualitative interviews with PWDs, key informant interviews with urban planning and tourism experts, local government officials, and heads of PWD Affairs Offices (PDAO), along with a quantitative survey.

The participants were recruited from disability organizations, online platforms, community centers, and collaborating urban planning and tourism agencies. They participated in semi-structured interviews, key informant interviews, and completed a survey questionnaire. Qualitative interviews allowed the PWDs to share narratives about encounters with stigma, physical and social barriers, and coping strategies. The key informant interviews provided insights from stakeholders regarding accessibility policies, practices, and the social dimension of accessibility. The survey collected quantitative data on perceptions of accessibility, experiences with discrimination, and the impact on affordability of tourism experiences.

The research integrated the Input-Output-Outcome conceptual framework to analyze the interplay of the following: a) Input (1): Perceptions of stigma and accessibility (including experiences of discrimination, social attitudes, and the physical accessibility of tourism infrastructure); b) Output (O): Assessment of variable relationships within disability models (e.g., how social stigma and support systems impact accessibility and affordability, how functional limitations and mental health interact with stigma, and the role of physical accessibility and service proximity in affordability).; and c) Outcome (O): Improved accessibility and affordability for PWDs (measured by increased accessible infrastructure, enhanced social inclusion, reduced attitudinal barriers, improved psychological well-being, and reduced financial barriers).

The analysis explored the linkages among these mentioned elements, examining how perceptions of stigma and accessibility were shaped by various disability models and ultimately impact the inclusivity of tourism experiences for PWDs.

Research revealed that the factors that influenced the use of tourism infrastructure and public spaces are social, psychological and environmental. These factors are associated based on social-psychological interaction and environmental impact on psychology.

Further, the results revealed that the geospatial patterns in accessibility highlighted that urban centers had higher compliance with accessibility standards, while peripheral areas lacked adequate facilities. The availability of accessible activities strongly correlated with higher accessibility ratings.
Thesis
Keywords: People with disabilities -- Philippines -- Quezon City; Urban ecology (Sociology) -- Philippines -- Quezon City; Recreation areas and people with disabilities -- Philippines -- Quezon City